The Influence of COVID - 19 on the Reading Interest of 4th-Grade Elementary School Students - Putri, Nur Ayu Kinanti Agung; Maryanti, Rina; Wulandary, Verra; Irawan, Asep Rudi (Indonesian Journal of Multidiciplinary Research, 2021)
This study aims to determine the impact of COVID-19 on the reading interest of elementary school students. By using data collection through a google form. COVID-19 turns out not to create students ' interest in reading to decrease. After a given material was directly distributed, it raises students ' interest in reading. By providing the material in individuals then the presentation of the rose to 44.4%. The presentation rise students’ interest in reading. This happens because there is little research regarding the reading interest of 4th-grade elementary school students. The rising reading interest will bring up students’ interest. COVID-19 does not become a barrier to the students to keep reading.